Alliance Quebec Condemns the Office de la langue française's Attempt to Impose Francization Requirements on Commercial Websites Produced in Quebec - Alliance Quebec (AQ) (1999)

Johnson Wants to End SSJB-M Sponsorship of Fête Nationale Celebrations - Alliance Quebec (AQ) (1998)

Alliance Québec est satisfaite de la décision du CRTC sur TVA-CanWest - Alliance Quebec (AQ) (1997)

Alliance Quebec Pleased with CRTC Decision on TVACanWest - Alliance Quebec (AQ) (1997)

[Open Letter - Regarding Proposed CBC Cutbacks] - Committee for Anglophone Social Action (CASA); Voice of English-speaking Quebec (VEQ); Outaouais Alliance; Townshippers' Association; Alliance Quebec (AQ) (1996)

The Royal Commission on Broadcasting - The Canadian Home and School and Parent-Teacher Federation (1956)
The Canadian Home and School and Parent-Teacher Federation, representing 274,693 members organized in 3,672 local associations in nine provincial federations across Canada, (Newfoundland is not presentl:y organized as a Provincial Federation) is pleased to submit this statement of our views with respect to broadcasting in Canada under the terms of Order in Council P.C.1955-1796 of December 2nd,1955